INGO FELDHAUSEN, JAN FLIESSBACH Y MARIA DEL MAR VANRELL (EDS.) (2018): Methods in Prosody: A Romance Language Perspective (Studies in Laboratory Phonology 6), Berlin, Language Science Press. (Estudios de Fonética Experimental)
[to be added]